Complete laparoscopic and Da Vinci robot esophagogastric anastomosis double muscle flap plasty for radical resection of proximal gastric cancer - Yang, Dong; Liu, Yuanlin; Meng, Xiangyu; Xu, Xing; Wang, Chao; Zhang, Meng; Zhang, Tao (Frontiers in Oncology, 2024)
Objective: To investigate the application value of complete laparoscopy and Da Vinci robot esophagogastric anastomosis double muscle flap plasty in radical resection of proximal gastric cancer.Method: A retrospective descriptive study was used. 1. Transoperative,2. Postoperative, 3. Follow-up. In relation to follow-up, esophageal disease status reflux, anastomosis, nutritional status score, serum hemoglobin, tumor recurrence, and metastasis were investigated. The trans and postoperative variables were obtained from the clinical records and the patients were followed up in outpatient department and by telephone.Result: Among the 35 patients, 17 underwent robotic surgery and 18 underwent laparoscopic surgery. There were 29 males and 6 females. 1) Transoperative: Robotic surgery: The operation time was (305.59 ± 22.07) min, the esophagogastric anastomosis double muscle flap plasty time was (149.76 ± 14.91) min, the average number of lymph nodes cleared was 30, and the average intraoperative blood loss was 30 ml. Laparoscopic surgery: The mean operation time was 305.17 ± 26.92min, the operation time of esophagogastric anastomosis double muscle flap was (194.06 ± 22.52) min, the average number of lymph nodes cleared was 24, and the average intraoperative blood loss was 52.5 ml. 2) Postoperative: Robotic surgery: the average time for patients to have their first postoperative anal emission was 3 days, the average time to first postoperative feeding was 4 days, and the average length of hospitalization after surgery was 8 days. Laparoscopic surgery: the average time for patients to have their first postoperative anal emission was 5 days, the average time to first postoperative feeding was 6 days, the average length of hospitalization after surgery was 10 days. 3) Follow-up: The follow-up time ranged from 1 to 42 months, with a median follow-up time of 24 months.Complete Da Vinci robot and laparoscopic esophagogastric anastomosis double muscle flap plasty for radical resection of proximal gastric cancer can minimize surgical incision, reduce abdominal exposure, accelerate postoperative recovery of patients, and effectively prevent reflux esophagitis and maintain good hemoglobin concentration and nutritional status. The advantages of robotic surgery is less intraoperative bleeding and faster post-surgical recovery, but it is relatively more expensive.